Deadmonton : crime stories from Canada's murder city - Roth, Pamela, 1981- (University of Regina Press, 2016)
"In 2011, with forty-eight of its citizens coming to a sudden, violent end, Edmonton gained the moniker "Murder Capital of Canada." And it wasn't the first time the "City of Champions" snagged the title nobody wants to claim. It earned the distinction in 2005. Even in 1938, the city had a higher per capita murder rate than Chicago. In Deadmonton, former Sun reporter Pamela Roth takes a look at some of the city's most notorious murders, both solved and unsolved. With testimony from victims' relatives, these stories serve as a reminder of the horror that humans are capable of inflicting upon one another, and highlight the pain left in the wake of such crimes. Deadmonton also offers a glimpse into the lives of detectives working to bring closure to families and justice to victims."--